Analysis of the vertical structure of the atmospheric heating process and its seasonal variation over the Tibetan Plateau using a land data assimilation system. Issue 22 (21st November 2013) - Seto, Rie; Koike, Toshio; Rasmy, Mohamed
Abstract [1] The atmospheric heating process over the Tibetan Plateau (TP) in the premonsoon and mature monsoon seasons of 2008 and 2009 was investigated using radiosonde data and a land data assimilation system coupled with a mesoscale model (LDAS‐A), which assimilates microwave brightness temperature and accurately reproduces land and atmospheric states. Focusing on the temperature observed below 200 hPa, we found that there were warming and cooling periods alternately in the premonsoon season within a general warming trend, and the profiles of heating in the two seasons were reversed. Then we identified the vertical structure of each heating component: sensible heat (SH), latent heat (LH), and horizontal advection (Hadv), using the LDAS‐A in each season. The troposphere over the TP in warming periods was divided into three vertical layers in terms of the major heating process: SH transport below 450 hPa, LH from 450 to 250 hPa, and Hadv above 250 hPa. The SH and LH are transported by local convections. In contrast, the heat source for Hadv originated in the southwest of the plateau, related to synoptic‐scale circulations. Latent cooling with cloud evaporation and adiabatic cooling with convection negatively contributed to heating in the upper troposphere. In cooling periods, the vertical structure of each heating component was similar to that in warming periods, but net heating was reversed because of the influence of synoptic‐scale disturbances. In the mature monsoon season, warm Hadv in the upper troposphere rapidly weakened in response to the initial formation of the Tibetan High.